Transcriptome analyses of inhibitor-treated schistosome females provide evidence for cooperating Src-kinase and TGFβ receptor pathways controlling mitosis and eggshell formation. - Christin Buro (Public Library of Science (PLoS), 2013)
Schistosome parasites cause schistosomiasis, one of the most prevalent parasitemias worldwide affecting humans and animals. Constant pairing of schistosomes is essential for female sexual maturation and egg production, which causes pathogenesis. Female maturation involves signaling pathways controlling mitosis and differentiation within the gonads. In vitro studies had shown before that a Src-specific inhibitor, Herbimycin A (Herb A), and a TGFβ receptor (TβR) inhibitor (TRIKI) have physiological effects such as suppressed mitoses and egg production in paired females. As one Herb A target, the gonad-specifically expressed Src kinase SmTK3 was identified. Here, we comparatively analyzed the transcriptome profiles of Herb A- and TRIKI-treated females identifying transcriptional targets of Src-kinase and TβRI pathways. After demonstrating that TRIKI inhibits the schistosome TGFβreceptor SmTβRI by kinase assays in Xenopus oocytes, couples were treated with Herb A, TRIKI, or both inhibitors simultaneously in vitro. RNA was isolated from females for microarray hybridizations and transcription analyses. The obtained data were evaluated by Gene Ontology (GO) and Ingenuity Pathway Analysis (IPA), but also by manual classification and intersection analyses. Finally, extensive qPCR experiments were done to verify differential transcription of candidate genes under inhibitor influence but also to functionally reinforce specific physiological effects. A number of genes found to be differentially regulated are associated with mitosis and differentiation. Among these were calcium-associated genes and eggshell-forming genes. In situ hybridization confirmed transcription of genes coding for the calcium sensor hippocalcin, the calcium transporter ORAI-1, and the calcium-binding protein calmodulin-4 in the reproductive system pointing to a role of calcium in parasite reproduction. Functional qPCR results confirmed an inhibitor-influenced, varying dependence of the transcriptional activities of Smp14, Smp48, fs800, a predicted eggshell precursor protein and SmTYR1. The results show that eggshell-formation is regulated by at least two pathways cooperatively operating in a balanced manner to control egg production.